CTNI-16. NRG-RTOG 9802 OBSERVATION ARM - LONG TERM RESULT. (14th November 2022) - Iwamoto, Fabio; Polley, Mei-Yin; Shaw, Edward; Buckner, Jan; Barger, Geoffrey; Coons, Stephen; Ricci, Peter; Gilbert, Mark; Brown, Paul; Stelzer, Keith; Rogers, C Leland; Suh, John; et al.
Abstract: BACKGROUND: Radiation Therapy Oncology Group 9802 was a phase III trial for patients with centrally confirmed LGG (WHO grade II). Participants ³ 40 years or those with neurosurgeon defined less than gross total resection (GTR) were randomized to radiotherapy (RT) +/- PCV. In a separate cohort, adults age < 40 years with neurosurgeon defined GTR were observed by MRI every 6 months without adjuvant therapy. At last report, outcome for the observation cohort was immature with median follow-up of only 4.4 years. Here, we present mature outcomes for the observation arm. METHODS: Eligible adults (as above) were observed by MRI every 6 months. OS and PFS were estimated by Kaplan-Meier method and estimated hazard ratios to characterize the prognostic variables. RESULTS: There were 111 eligible patients (median age 30; median KPS = 100). Median follow-up was 16.1 years with 71 (64%) alive at the last follow-up. 79 patients (71%) had progressed with median PFS of 6.9 years. 5, 10, and 15 year-PFS and OS rates were 54%, 39%, 28% and 94%, 77%, and 65%. 1p19q status was codeleted in 32%, IDH1/2 mutant in 78% and MGMT promoter methylated in 39% of tested cases. Multivariate Cox analyses showed that preoperative tumor size ³ 4 cm (HR = 2.43 for PFS, p = 0.001; HR = 2.58 for death, p = 0.016) and residual disease on imaging ³ 1 cm (HR = 2.97 for PFS, P < 0.001; HR = 2.02 for death, p = 0.05) were associated with worse outcomes. Analyses based on molecular results will be presented. CONCLUSION: A subset of low-grade gliomas can be observed after the initial resection based on younger age, smaller tumor size, and no residual disease on neuroimaging. This can likely be further refined by prognostic molecular markers. Patients with the most favorable prognostic factors can avoid or delay the acute and long-term side effects of RT and chemotherapy for several years.